2017
DOI: 10.3389/fneur.2017.00318
|View full text |Cite
|
Sign up to set email alerts
|

Non-Syndromic Spinal Schwannomas: A Novel Classification

Abstract: Schwannomas are the most frequent primary tumors of the spine with an incidence of 0.3–0.5/100,000 person per year. Current treatment for non-syndromic spinal schwannomas is total resection of the tumor with preservation of neurovascular structures. This study aims to report neurologic and radiologic outcome following treatment of non-syndromic spinal schwannomas along with a novel tumor classification used in our clinic. A retrospective case series was carried out with a patient sample of 82 male and female p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 33 publications
0
25
0
1
Order By: Relevance
“…Schwannomas are the most frequent peripheral nerve sheath tumors, representing one of the primary benign spinal tumors [5] , [6] , [7] , [8] . Generally, they are diagnosed in the fourth or fifth decade of life and affect males and females equally [ 4 , 6 , 7 ]. However, a few studies have recently suggested a slight male predilection [ 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schwannomas are the most frequent peripheral nerve sheath tumors, representing one of the primary benign spinal tumors [5] , [6] , [7] , [8] . Generally, they are diagnosed in the fourth or fifth decade of life and affect males and females equally [ 4 , 6 , 7 ]. However, a few studies have recently suggested a slight male predilection [ 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of spinal schwannomas varies with age. The peak incidence is in the fourth to fifth decade of life [ 9 , 10 ]. There was no reported correlation between the prevalence of this tumor and sex.…”
Section: Discussionmentioning
confidence: 99%
“…When arising from spinal nerves, radiculopathy is the typical presentation, beginning with dermatomal pain, which may evolve into progressive focal motor weakness as the tumor grows and mass effect increases [10]. MRI findings include a characteristically well-circumscribed, contrast-enhancing mass, with T2 hyperintensity, and frequent involvement of the neural foramen at the level of disease [2]. More than 95% of spinal schwannomas occur sporadically; however, several distinct syndromic presentations are frequently observed [11].…”
Section: Discussionmentioning
confidence: 99%